2013
DOI: 10.1159/000354546
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcome after Combination Therapy for Polypoidal Choroidal Vasculopathy: Comparison with Photodynamic Monotherapy and Anti-Vascular Endothelial Growth Factor Monotherapy

Abstract: Purpose: To compare treatment outcomes of photodynamic therapy (PDT), anti-vascular endothelial growth factor (VEGF) therapy and PDT combined with anti-VEGF therapy for polypoidal choroidal vasculopathy (PCV). Procedures: A total of 62 eyes of 62 patients who had completed at least 2 years of follow-up were retrospectively reviewed; 19 eyes received PDT only, 23 had anti-VEGF therapy only and 20 underwent combination therapy. Best-corrected visual acuity at baseline and each follow-up visit was investigated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Treatment of PCV is complex and based on visual acuity (VA), location of the PCV complex and treatment response. Various treatment options for PCV exist, including photodynamic therapy (PDT) (Visudyne, verteporfin, Bausch & Lomb, Rochester, New York, USA),5–7 anti-VEGF (vascular endothelial growth factor) therapy8 9 and combination therapy 10. The EVEREST clinical trial11 was a landmark prospective study of PCV treatment that compared PDT alone, anti-VEGF therapy alone and PDT in combination with anti-VEGF therapy.…”
mentioning
confidence: 99%
“…Treatment of PCV is complex and based on visual acuity (VA), location of the PCV complex and treatment response. Various treatment options for PCV exist, including photodynamic therapy (PDT) (Visudyne, verteporfin, Bausch & Lomb, Rochester, New York, USA),5–7 anti-VEGF (vascular endothelial growth factor) therapy8 9 and combination therapy 10. The EVEREST clinical trial11 was a landmark prospective study of PCV treatment that compared PDT alone, anti-VEGF therapy alone and PDT in combination with anti-VEGF therapy.…”
mentioning
confidence: 99%
“…Among them, two articles were excluded as case reports, and two articles were excluded because they included additional treatment strategies for PCV. A final total of 22 studies were included in the present meta‐analysis. The study selection process is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of patients across all studies ranged from 53 to 75.8 years, while study duration ranged from 1 to 36 months. Among the included studies were three RCTs and 19 retrospective comparative studies . Specific interventions and pro re nata (PRN) retreatment regimen used within each trial are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations